PRIMARY MESENTERIC VENOUS THROMBOSIS - REPORT OF A CASE - (:unkn) unknown (SPRINGER VERLAG, 1994)
Two patients suffering from a small bowel infarction due to a primary mesenteric venous thrombosis are herein presented. One patient was a 38-year-old woman while the other was a 54-year-old man. An accurate diagnosis could not be made before operation. In both cases, the necrotic bowel was resected and a primary anastomosis was established. A second laparatomy and resection of a reinfarcted small bowel was necessary in one patient. Both patients were later discharged under a regimen of indefinite warfarin therapy.
Keywords: SUPERIOR MESENTERIC VENOUS THROMBOSIS; SMALL BOWEL NECROSIS